The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

The Twenty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2003)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

The Twenty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2006)

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

The Twenty-Eighth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2009)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

The English Speaking Catholic Council: The Thirty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (2016)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

Report on the Proposed Ethics and Religious Culture Program - The English Speaking Catholic Council (ESCC) (2006)
We affirm the positive objectives of this program, namely: 1) To incorporate ethics and religion into public education; 2) To foster students’ capacity to know and express their moral and religious convictions within a pluralistic context; 3) To develop the capacity for meaningful dialogue about diverse moral and religious convictions; 4) To anchor this program in the distinctive cultural and religious heritage of Quebec. However, we recommend some major revisions to the program. Five interrelated areas stand out for us.

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.